Helicity wave functions for massless and massive spin-2 particles - Spehler, D. [UNESP]; Novaes, S. F. [UNESP] (American Physical Society (APS), 1991)
Starting from general properties of a spin-2 field, we construct helicity wave functions in the framework of the Weyl-van der Waerden spinor formalism. We discuss here the cases of massless and massive spin-2 particles. © 1991 The American Physical Society.